Meningkatkan Hasil Belajar Bola Voli Melalui Modifikasi Peraturan dengan Menggunakan Media Video - Nugroho, Agung Tri (Department of Physical Education, Sport, Health and Recreation, 2015)
Researchers is to determine whether to modify the rules and using video media can improve learning outcomes of students in volleyball at SMK Negeri 1 Sedan Regency Rembang year 2013/2014. This study is anexamination of class action (PTK) in which there are two siklus.The results showed that before applying thereflective learning or students who complete the initial data is only 19.35% (4). Once applied reflective learningin learning volleyball on students who complete the first cycle of 51.61% (17 people), so there is an increasefrom the initial data with the percentage of 32.26%. In the second cycle the number of students who complete apercentage of 87.09% (27 people), and has increased from the first cycle of 35.48%. Based on our results it can be concluded that the modification rules of the game in the volleyball learning can improve student learning outcomes volleyball at SMK Negeri 1 Sedan, Thus said the study results.